The Inheritance and Innovation of Modern Mongolian Dance: A Case Study of "Ben Teng" - Chen, Yuxuan; Moonsuwan, Thanyalak (Journal of Posthumanism, 2025)
The inheritance and innovation of modern Mongolian dance represent critical areas in preserving and developing cultural heritage. This study analyzes “Ben Teng,” a representative modern Mongolian dance piece, to explore the balance between traditional elements and innovative expression in contemporary choreography. This research investigates how “Ben Teng” integrates classical Mongolian movements with modern techniques by employing qualitative methods such as participant observation, expert interviews, and video analysis. The findings highlight the adaptive strategies dancers and choreographers use to maintain cultural continuity while embracing creative evolution. The results indicate that contemporary Mongolian dance preserves cultural identity and contributes to expanding the artistic repertoire through innovative practices. This paper discusses the significance of these findings in the broader context of cultural preservation and artistic innovation, proposing recommendations for future choreographic practices and cultural policies.